Tax Planning and Corporate Value: The Role of Firm Size as a Moderation Variable in Energy Companies - Nurlaili, Heny; Maisyarah, Renny; Nasution, M. Irsan (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to analyze the influence of tax planning on the value of companies with firm size as a moderation variable in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. This research is motivated by fluctuations in the value of companies in the energy sector and the inconsistency of previous research results regarding the relationship between tax planning and company value. The research uses a quantitative approach with secondary data obtained from financial statements and annual reports. The research sample consisted of 24 energy sector companies selected using purposive sampling techniques, so that data was obtained from 120 observations. Data analysis was carried out using panel data regression with Moderated Regression Analysis (MRA). The company's value is proxied by Price to Book Value (PBV), tax planning is measured using the Effective Tax Rate (ETR), and firm size is measured by the natural logarithm of total assets. The results of the study show that tax planning has a positive effect on the value of the company. However, firm size has not been proven to be able to moderate the influence of tax planning on company value. These findings suggest that while tax planning can increase a company's value, company size does not significantly strengthen or weaken the relationship in the corporate context of the energy sector.